2021
DOI: 10.1038/s41467-021-25191-5
|View full text |Cite
|
Sign up to set email alerts
|

The cytokines HGF and CXCL13 predict the severity and the mortality in COVID-19 patients

Abstract: The objective of the present study was to identify biological signatures of severe coronavirus disease 2019 (COVID-19) predictive of admission in the intensive care unit (ICU). Over 170 immunological markers were investigated in a ‘discovery’ cohort (n = 98 patients) of the Lausanne University Hospital (LUH-1). Here we report that 13 out of 49 cytokines were significantly associated with ICU admission in the three cohorts (P < 0.05 to P < 0.001), while cellular immunological markers lacked power in discr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
73
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(82 citation statements)
references
References 63 publications
9
73
0
Order By: Relevance
“…As reported previously, plasma IL-6, IL-8, EN-RAGE, HGF, VEGFA, PD-L1 and TNFRSF12A levels were associated with COVID-19 severity (8) and distinct from ICs (Figure S4A) , which lacked peripheral inflammation. Plasma TNFRSF11B, EZR and CCL23 were increased in class III vs ICs (Figure S4A) .…”
Section: Resultssupporting
confidence: 81%
“…As reported previously, plasma IL-6, IL-8, EN-RAGE, HGF, VEGFA, PD-L1 and TNFRSF12A levels were associated with COVID-19 severity (8) and distinct from ICs (Figure S4A) , which lacked peripheral inflammation. Plasma TNFRSF11B, EZR and CCL23 were increased in class III vs ICs (Figure S4A) .…”
Section: Resultssupporting
confidence: 81%
“…Besides these, the clinical trials in sepsis patients revealed that IL-6 is a predominant inflammatory mediator of cytokine-driven coagulation than both TNF-α and IL-1 that are strongly upregulated during SARS-CoV-2 infection [95] . Concerning growth factors, a recent study has shown an association of a high level of HGF with severity and mortality of COVID-19 patients [77] . These findings indicate the existence of a possible interplay between Inflammation and coagulation during SARS-CoV-2 infection.…”
Section: Sars-cov-2 Induced Inflammation and Coagulopathymentioning
confidence: 99%
“…Most commonly identified inflammatory factors including IL-2, IL-6, IL-7, IL-8 (CXCL8), TNF-α, granulocyte-colony stimulating factor (G-CSF), chemokine interferon-c inducible protein-10 (IP-10, CXCL10), CCL2 (MCP-1), MIP1α/CCL3 and CRP, procalcitonin (PCT), and ferritin [10] , [73] , [74] , [75] secreted by the infected cells and, immune cells recruit both innate and adaptive immune cells to the site of infection, thereby, exacerbating inflammatory responses [76] . In addition, a recent study highlighted the induction of hepatocyte growth factor (HGF) as counter-mechanism to resist pro- cytokine-mediated inflammation in severe COVID-19 [77] . Among the proinflammatory cytokines, IL-6 has been identified as the most common and predominant cytokine causing the cytokine storm [13] , a phenomenon behind acute lung injury and ARDS in severe COVID-19 cases.…”
Section: Sars-cov-2 Induced Inflammation and Coagulopathymentioning
confidence: 99%
“…We live in a world where scientific publishing and thus peer review have become a major determinant of career development and success or failure (Neill 2008 ; Fanelli 2010 ; Van Wesel 2016 ; Fanelli and Larivière 2016 ; Vuong 2019 ). Improvement of humans’ daily lives and advancement of societies also depend upon the production of scientific knowledge and dissemination of research results (Böhme and Stehr 1986 ; Stehr 2009 ; de Camargo Jr 2011 ; Thorlindsson and Vilhjalmsson 2016 ), which often are the only means by which humanity can manage and overcome global crises, such as the current COVID-19 pandemic due to the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) (Hu et al 2020 ; COVID- 19 Host Genetics Initiative 2021 ; Perreau et al 2021 ; Solís et al 2021 ; Telenti et al 2021 ).…”
Section: Introductionmentioning
confidence: 99%